Super-high-resolution aerial imagery, digital surface models and 3D point clouds of Meade Fire Scar, Alaska - Tabea Rettelbach; Ingmar Nitze; Inge Grünberg; Jennika Hammar; Simon Schäffler; Daniel Hein; Matthias Gessner; Tilman Bucher; Jörg Brauchle; Jörg Hartmann; Torsten Sachs; Julia Boike; et al. (PANGAEA, 2024)
As part of the ThawTrend-Air airborne campaign led by the Alfred Wegener Institute in 2019, we collected super-high-resolution multispectral imagery of permafrost landscapes with the Modular Aerial Camera System (MACS), developed by the German Aerospace Center. From these images, we photogrammetrically processed four-band orthophotos (blue, green, red, near-infrared) and digital surface models at very high spatial resolution of 10 cm, as well as photogrammetric point clouds in RGB and NIR. This data collection aggregates two data subsets of the Imuruk volcanic field on the northern Seward Peninsula, Alaska, covering approximately 50 km^2. All images were collected on 10 July 2021.